2011
DOI: 10.1124/jpet.111.188441
|View full text |Cite
|
Sign up to set email alerts
|

Specific Inhibition of Spleen Tyrosine Kinase Suppresses Leukocyte Immune Function and Inflammation in Animal Models of Rheumatoid Arthritis

Abstract: Based on genetic studies that establish the role of spleen tyrosine kinase (Syk) in immune function, inhibitors of this kinase are being investigated as therapeutic agents for inflammatory diseases. Because genetic studies eliminate both adapter functions and kinase activity of Syk, it is difficult to delineate the effect of kinase inhibition alone as would be the goal with small-molecule kinase inhibitors. We tested the hypothesis that specific pharmacological inhibition of Syk activity retains the immunomodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 36 publications
3
103
1
Order By: Relevance
“…S1B). This SYK inhibitor has been validated in previous studies, where it showed suppression of BCR-dependent SYK activity in B cells (18,19). Upon induction of shRNAs targeting CD79a in DG75 cells, we observed a profound reduction of CD79a expression leading to diminished expression of BCR on the cell surface ( Fig.…”
Section: Resultsmentioning
confidence: 65%
“…S1B). This SYK inhibitor has been validated in previous studies, where it showed suppression of BCR-dependent SYK activity in B cells (18,19). Upon induction of shRNAs targeting CD79a in DG75 cells, we observed a profound reduction of CD79a expression leading to diminished expression of BCR on the cell surface ( Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Indeed, small-molecule compounds targeting kinase proteins are emerging as potential treatments for RA because multiple signaling kinases are involved in the pathogenesis of RA, and such inhibitors can be designed to recognize particular conformations of their targets (Pesu et al, 2008;Cohen and Fleischmann, 2010;Kyttaris, 2012;Meier and McInnes, 2014). For example, inhibitors of IkB kinase (IKK)-2, glycogen synthase kinase (GSK)-3b, c-Fms tyrosine kinase, spleen tyrosine kinase, Bruton's tyrosine kinase (Btk), phosphatidylinositol-3 kinases, and Janus kinases (JAKs) have been reported to be efficacious in animal models of RA (Podolin et al, 2005;Cuzzocrea et al, 2006;Toyama et al, 2010;Dehlin et al, 2011;Coffey et al, 2012;Xu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The structure identity and quality of PRT062070 was confirmed by high-performance liquid chromatography, Fourier transform infrared spectroscopy, highresolution mass spectroscopy, and proton NMR. Potency against purified SYK was determined by fluorescence resonance energy transfer as previously described (Coffey et al, 2012). A broader panel of 270 purified kinases (EMD Milipore, Billerica, MA) was surveyed in which PRT062070 was tested at a fixed concentration of 300 nM.…”
Section: Methodsmentioning
confidence: 99%
“…SYK is required for signaling and immune cell activation via the B-cell antigen receptor (BCR), activating fragment crystallizable receptors, and integrins (Mocsai et al, 2010). Genetic studies demonstrate SYK is required for certain inflammatory and autoimmune mechanisms in mice (Colonna et al, 2010;Jakus et al, 2010;Elliott et al, 2011;Wex et al, 2011;Ozaki et al, 2012), a concept that has been reproduced pharmacologically in cellular and animal models (Braselmann et al, 2006;Pine et al, 2007;Coffey et al, 2012). Phase II clinical trials of SYK inhibition by R788 [(6-(5-fluoro-2-(3,4,5-trimethoxyphenylamino)pyrimidin-4-ylamino)-2,2-dimethyl-3-oxo-2,3-dihydropyrido [3,2-b][1,4]oxazin-4-yl)methyl dihydrogen phosphate] demonstrated efficacy in B-cell non-Hodgkin lymphoma (NHL) and chronic lymphocytic leukemia (CLL) (Friedberg et al, 2010), rheumatoid arthritis (RA) (Weinblatt et al, 2008(Weinblatt et al, , 2010, and immune thrombocytopenia (Podolanczuk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%